Pneumococcal conjugate vaccine 13 delivered as one primary and one booster dose (1 + 1) compared with two primary doses and a booster (2 + 1) in UK infants: a multicentre, parallel group randomised controlled trial. Issue 2 (February 2018) - Goldblatt, David; Southern, Jo; Andrews, Nick J; Burbidge, Polly; Partington, Jo; Roalfe, Lucy; Valente Pinto, Marta; Thalasselis, Vasilli; Plested, Emma; Richardson, Hayley; Snape, Matthew D; Miller, Elizabeth
Summary: Background: Infants in the UK were first offered a pneumococcal conjugate vaccine (PCV7) in 2006, given at 2 and 4 months of age and a booster dose at 13 months (2 + 1 schedule). A 13-valent vaccine (PCV13) replaced PCV7 in 2010. We aimed to compare the post-booster antibody response in UK infants given a reduced priming schedule of PCV13 (ie, a 1 + 1 schedule) versus the current 2 + 1 schedule and to assess the potential effect on population protection. Methods: In this multicentre, parallel group, randomised controlled trial, we recuited infants due to receive their primary immunisations aged up to 13 weeks on first vaccinations by information booklets mailed out via the NHS Child Health Information Service and the UK National Health Application and Infrastructure Services. Eligible infants were randomly assigned (1:1) to receive PCV13 at 2, 4, and 12 months (2 + 1 schedule) or 3 and 12 months of age (1 + 1 schedule) delivered with other routine vaccinations. Randomisation was done by computer-generated permuted block randomisation, with a block size of six. Participants and clinical trial staff were not masked to treatment allocation. The primary endpoint was serotype-specific immunoglobulin G concentrations values (geometric mean concentrations [GMC] in μg/mL) measured in blood samples collected at 13 months of age. Analysis was by modified intention to treat with all individuals included by randomised group if they had a laboratory result. This trial is registered on the EudraCT clinical trial database, number 2015-000817-32, and ClinicalTrials.gov, number NCT02482636 . Findings: Between September, 2015, and June, 2016, 376 infants were assessed for eligibility. 81 infants were excluded for not meeting the inclusion criteria (n=50) or for other reasons (n=31). 213 eligible infants were enrolled and randomly allocated to group 1 (n=106; 2 + 1 schedule) or to group 2 (n=107; 1 + 1 schedule). In group 1, 91 serum samples were available for analysis 1 month after booster immunisation versus 86 in group 2. At month 13, post-booster, GMCs were equivalent between schedules for serotypes 3 (0·61 μg/mL in group 1 vs 0·62 μg/mL in group 2), 5 (1·74 μg/mL vs 2·11 μg/mL), 7F (3·98 μg/mL vs 3·36 μg/mL), 9V (2·34 μg/mL vs 2·50 μg/mL), and 19A (8·38 μg/mL vs 8·83 μg/mL). Infants given the 1 + 1 schedule had significantly greater immunogenicity post-booster than those given the 2 + 1 schedule for serotypes 1 (8·92 μg/mL vs 3·07 μg/mL), 4 (3·43 μg/mL vs 2·55 μg/mL), 14 (16·9 μg/mL vs 10·49 μg/mL), and 19F (14·76 μg/mL vs 11·12 μg/mL; adjusted p value range <0·001 to 0·047). The 2 + 1 schedule was superior for serotypes 6A, 6B, 18C and 23F (adjusted p value range <0·0001 to 0·017). In a predefined numerical subset of all of the infants recruited to the study (n=40 [20%]), functional serotype-specific antibody was similar between schedules. 26 serious adverse events were recorded in 21 (10%) infants across the study period; 18 (n=13) were in the 2 + 1 group and eight (n=8) in the 1 + 1 group. Only one serious adverse event, a high temperature and refusal to feed after the first vaccination visit in a child on the 2+1 schedule was considered related to vaccine. Interpretation: Our findings show that for nine of the 13 serotypes in PCV13, post-booster responses in infants primed with a single dose are equivalent or superior to those seen following the standard UK 2 + 1 schedule. Introducing a 1 + 1 schedule in countries with a mature PCV programme and established herd immunity is likely to maintain population control of vaccine-type pneumococcal disease. Funding: NIHR and the Bill & Melinda Gates Foundation .